Relationship between K-line distance and surgical outcome in cases of laminoplasty for cervical ossification of the posterior longitudinal ligament. Issue 47 (25th November 2022) - Miyazaki, Masashi; Ishihara, Toshinobu; Kanezaki, Shozo; Hirakawa, Masashi; Iwasaki, Tatsuya; Abe, Tetsutaro; Tsumura, Hiroshi
Abstract : Although previous studies indicate that changes in cervical alignment after laminoplasty and dynamic factors influence surgical outcomes of cervical ossification of the posterior longitudinal ligament (OPLL), the relationship between the surgical outcomes, the distance between the kyphosis-line (K-line) and OPLL, and dynamic factors have not yet been quantitatively evaluated. The purpose of the present study was to analyze the relationship between ΔK-line distance and surgical outcomes in cases of laminoplasty for OPLL of the cervical spine. We retrospectively reviewed 46 consecutive patients (33 men and 13 women) with cervical OPLL who underwent laminoplasty. "K-line distance" was measured as the minimum interval between the K-line and OPLL on lateral radiographs. The following factors were analyzed: K-line distance in neutral, flexion, and extension neck positions, ΔK-line distance, preoperative C2-7 range of motion (ROM), preoperative segmental ROM, preoperative C2-7 lordotic angle, occupying ratio of the OPLL, disease duration, preoperative and postoperative Japanese Orthopaedic Association (JOA) score, and recovery rate. Patients were divided into flexion K-line (+) and flexion K-line (−) groups. We then analyzed the influence of the K-line distance on surgical outcomes and conducted multivariate analysis to analyze the factors affecting surgical outcomes. The JOA score recovery rate in the flexion K-line (−) group was significantly lower than that in the flexion K-line (+) group ( P  = .024). The ΔK-line distance was significantly negatively correlated with the JOA score recovery rate (r = −0.531, P  < .001). Additionally, multivariate analysis showed that ΔK-line distance (OR = −2.143, P  = .015) was negatively correlated with the JOA score recovery rate. The ΔK-line distance is considered useful for the quantitative evaluation of dynamic factors and static compression factors due to OPLL through the measurement of dynamic radiographic images.